2009
DOI: 10.1016/j.coph.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G: a human pregnancy-related immunomodulator

Abstract: In human pregnancies mothers and their embryo/fetuses are invariably genetically different. Thus, attenuation of the adaptive maternal immune response, which is programmed to reject “foreign” entities, is required for pregnancy to be initiated and maintained. Unexpectedly, given the propensity of the immune system to dispose of non-self entities, at least 50% of expected human pregnancies reliably go forward. This indicates that to a large extent, effective systems of tolerance have evolved. Although overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 50 publications
1
60
0
3
Order By: Relevance
“…However, this physiology requires development of immunologic mechanisms whereby the semiallogeneic fetus escapes recognition by the maternal immune system. This requirement provides for the expression on the placenta of nonclassical MHC class I HLA-G, which stimulates inhibitory receptors on cells of lymphoid and myelomonocytic origin (54,55). It also selects for the production of immune inhibitory cytokines, PGs, and immunoregulatory T cells (56,57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this physiology requires development of immunologic mechanisms whereby the semiallogeneic fetus escapes recognition by the maternal immune system. This requirement provides for the expression on the placenta of nonclassical MHC class I HLA-G, which stimulates inhibitory receptors on cells of lymphoid and myelomonocytic origin (54,55). It also selects for the production of immune inhibitory cytokines, PGs, and immunoregulatory T cells (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Three peptides corresponding to N-and C-terminal regions of PfP0 were synthesized and purified to 70-80% (Chiron, Clayton, Victoria, Australia). The peptides were designated N1 (DNVGSNQMASVRKSLR; codons 33-48), N2 (SV-RKSLRGKATILMGKNT; codons [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], and C1 (AKADEPKKEE-AKKVE; codons 285-299) and correspond to T cell epitopes identified by lymphocyte proliferation responses of immunized mice (41). PHA (Sigma-Aldrich) or anti-CD3/28-coated T cell expander beads (Dynal) were used as positive controls.…”
Section: Ags and Mitogensmentioning
confidence: 99%
“…Other candidates responsible for the cytokine profile of the decidual T cells could be molecules expressed/produced by trophoblasts. Soluble HLA-G5, secreted by the villous and extravillous cytotrophoblast that are, respectively, in direct contact with maternal blood of the intervillous space and maternal T cells in the decidua basalis (13), could be one of these.…”
mentioning
confidence: 99%
“…However, the antibody used to identify these antigens required MHC light chain and MHC heavy chain associations which are not present on all HLA-G isoforms. More recent studies using different antibodies which are capable of detecting previously undetectable HLA-G alleles showed that HLA-G isoforms are present throughout the placenta and within the chorion membrane, decidua and maternal blood (Hunt and Langat, 2009). …”
Section: Major Histocompatibility Complex (Mhc) and The Non-classicalmentioning
confidence: 99%
“…Early studies identified HLA class I antigen expression as being specific to extra-villous trophoblast (EVT) populations, with the proteins being prominent in cells adjacent to the decidua throughout gestation (Hunt and Langat, 2009). However, the antibody used to identify these antigens required MHC light chain and MHC heavy chain associations which are not present on all HLA-G isoforms.…”
Section: Major Histocompatibility Complex (Mhc) and The Non-classicalmentioning
confidence: 99%